Faktor-Faktor yang Berhubungan dengan Kepatuhan Kontrol pada Penderita Diabetes Melitus Tipe 2 di Puskesmas Teluk Dalam Banjarmasin - Rosela Elmita; Syamsul Arifin; Lena Rosida (Homeostasis, 2019)
Abstract: Adherence control is influenced by work, family’s income, educational level, patient perception of the medical staffs’ attitude and family support. The study aimed to analyze factors associated with adherence of control in patients with type 2 Diabetes Mellitus in Puskesmas Teluk Dalam Banjarmasin. Research Methodology used is observational analytic research method with cross sectional approach. The sample consisted of 50 respondents. Data was collected by systematic random sampling technique. The chi square test with α <0.05 used by the researcher for the data analysis. Results showed that unemployment respondents (76%) have a high adherence to control (ρ=0.027, PR=2.77), low income respondents (52%) have a adherence to control (ρ=0.095), respondents with higher educational (56%) have high adherence to control  (ρ=0.002, PR=5.09), respondents with good perceptions of amedical staffs’ attitudes  (78%) have  high adherence to control (ρ=0.010, PR = 3.1) and respondents with a good family support (70%) have high adherence to control (ρ=0.006, PR=3.5). There are some factors that influenced the adherence to control in patients with type 2 diabetes mellitus in Puskesmas Teluk Dalam Banjarmasin which are work, educational level, patient perceptions of the medical staffs’ attitude, and family support. Factor is not related to adherence control is family’s income. Keywords: Adherence control of diabetes mellitus patients, educational level, patient perceptions attitude, family support, family’s income. Abstrak: Kepatuhan kontrol dipengaruhi oleh pekerjaan, pendapatan, pendidikan, persepsi pasien terhadap sikap tenaga kesehatan dan dukungan keluarga. Penelitian bertujuan menganalisis faktor-faktor yang berhubungan dengan kepatuhan kontrol pada penderita DM tipe 2 di Puskesmas Teluk Dalam Banjarmasin. Metode penelitian observasional analitik dengan pendekatan cross sectional. Sampel berjumlah 50 responden diambil dengan teknik systematic random sampling. Analisis data menggunakan uji chi square dengan α<0,05. Hasil penelitian menunjukan responden tidak bekerja (76%) lebih patuh kontrol (ρ=0,027, PR=2,77), responden pendapatan rendah (52%) memiliki perilaku patuh kontrol (ρ=0,095), responden dengan pendidikan tinggi (56%) lebih patuh melakukan kontrol (ρ=0,002, PR=5,09), responden dengan persepsi pasien terhadap sikap tenaga kesehatan baik (78%) lebih patuh kontrol (ρ=0,010, PR=3,1) dan responden dengan dukungan kelurga baik (70%) lebih patuh melakukan kontrol (ρ=0,006, PR=3,5). Kesimpulan penelitian faktor-faktor yang terdapat hubungan dengan kepatuhan kontrol pada penderita diabetes melitus tipe 2 di Puskesmas Teluk Dalam Banjarmasin adalah pekerjaan, pendidikan, persepsi pasien terhadap sikap tenaga kesehatan, dan dukungan keluarga. Faktor yang tidak berhubungan dengan kepatuhan kontrol pada penderita diabetes melitus tipe 2 di Puskesmas Teluk Dalam Banjarmasin adalah pendapatan. Kata-kata kunci: kepatuhan kontrol penderita diabetes melitus, pendidikan, persepsi pasien terhadap sikap tenaga kesehatan, dukungan keluarga, pendapatan.